Chronological Monte Carlo-based assessment of distribution system reliability - Leite da Silva, Armando M.; Cassula, Agnelo M. [UNESP]; Nascimento, Luiz C.; Freire, Jose C. [UNESP]; Sacramento, Cleber E.; Guimaraes, Ana Carolina R.; IEEE (Ieee, 2006)
Regulatory authorities in many countries, in order to maintain an acceptable balance between appropriate customer service qualities and costs, are introducing a performance-based regulation. These regulations impose penalties, and in some cases rewards, which introduce a component of financial risk to an electric power utility due to the uncertainty associated with preserving a specific level of system reliability. In Brazil, for instance, one of the reliability indices receiving special attention by the utilities is the Maximum Continuous Interruption Duration per customer (MCID). This paper describes a chronological Monte Carlo simulation approach to evaluate probability distributions of reliability indices, including the MCID, and the corresponding penalties. In order to get the desired efficiency, modern computational techniques are used for modeling (UML - Unified Modeling Language) as well as for programming (Object- Oriented Programming). Case studies on a simple distribution network and on real Brazilian distribution systems are presented and discussed.
Keywords: distribution reliability; object-oriented programming; Markov chains; Monte Carlo simulation